The complete archaeology of Greece : from hunter-gatherers to the 20th century AD - Bintliff, J. L. (John L.); Wiley InterScience (Online service) (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2012)
"The Complete Archaeology of Greece covers the incredible richness and variety of Greek culture and its central role in our understanding of European civilization, from the Palaeolithic era of 400,000 years ago to the early modern period. In a single volume, the field's traditional focus on art and architecture has been combined with a rigorous overview of the latest archaeological evidence forming a truly comprehensive work on Greek civilization. A unique single-volume exploration of the extraordinary development of human society in Greece from the earliest human traces up till the early 20th century AD Provides 22 chapters and an introduction chronologically surveying the phases of Greek culture, with over 200 illustrations Features over 200 images of art, architecture, and ancient texts, and integrates new archaeological discoveries for a more detailed picture of the Greece past, its landscape, and its people Explains how scientific advances in archaeology have provided a broader perspective on Greek prehistory and history Offers extensive notes on the text, available online, including additional details and references for the serious researcher and amateur"--
The landscape and Aegean prehistory -- The archaeology of Classical, Hellenistic, and Roman Greece in its longer-term context -- The archaeology of medieval and post-medieval Greece in its historical context.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Greece -- Antiquities; Greece -- Civilization; Architecture, Ancient -- Greece; Art, Ancient -- Greece; Excavations (Archaeology) -- Greece; SOCIAL SCIENCE -- Archaeology; Antiquities; Architecture, Ancient; Art, Ancient; Civilization; Excavations (Archaeology); Greece; Ausgrabung; Griechenland; Electronic books